APEC: INDONESIA AS A BALANCER AMONG US-CHINA - Adellia Monika (Kajian Asia Pasifik, 2020)
APEC is an international organization located in the Asia Pacific region. Its member countries are affiliated with the intention of not only developing the regional economy but also making the region stable, because the Asia Pacific region is a busy area visited by international community entities, from developed to developing countries. This research will discuss the role of Indonesia as a counterweight to the interests of the United States and the People's Republic of China, especially in the economic fields of which each country is incorporated in APEC. Because, we know the dominance of the policies issued by the United States and the People's Republic of China in recent years has been very influential both in the international and regional order. The method used is qualitative by conducting a literature study. The approach or theory used in analyzing the discussion is the Concept of Interdependence and Neoliberal Institutionalism. The purpose of this study is to examine the extent of Indonesia's role in efforts to create regional stability between two countries that have more power such as the United States and the People's Republic of China. The results of this study will outline the benefits, opportunities and challenges of Indonesia in APEC membership and its impact on its relationship with the United States and the People's Republic of China. Keywords: APEC, Interdependence, Neoliberal Institutionalism, Indonesia, United States, China Abstrak APEC adalah salah satu organisasi internasional yang berada di kawasan Asia Pasifik. Negara-negara anggotanya tergabung dengan maksud tidak hanya mengembangkan ekonomi kawasan tapi juga menjadikan kawasan tersebut stabil, sebab kawasan Asia Pasifik merupakan kawasan yang ramai disinggahi para entitas masyarakat internasional, dari negara-negara maju hingga berkembang. Penelitian ini akan membahas mengenai peran Indonesia sebagai penyeimbang kepentingan Amerika Serikat dan Republik Rakyat Tiongkok, terutama di bidang ekonomi yang masing-masing negara tersebut tergabung dalam APEC. Sebab, kita ketahui dominasi dari adanya kebijakan yang dikeluarkan oleh Amerika Serikat dan Republik Rakyat Tiongkok beberapa tahun terakhir ini sangat berpengaruh baik di tatanan internasional maupun kawasan. Metode yang digunakan adalah kualitatif dengan melakukan studi literatur. Pendekatan atau teori yang digunakan dalam menganalisa pembahasan adalah Konsep Interdependensi dan Neoliberal Institusionalisme. Tujuan Penelitian ini adalah meninjau sejauh mana peran Indonesia dalam upaya menciptakan stabilitas kawasan di antara dua negara yang memiliki power lebih seperti Amerika Serikat dan Republik Rakyat Tiongkok. Hasil penelitian ini akan menguraikan manfaat, peluang dan tantangan Indonesia dalam keanggotaan APEC serta dampaknya terhadap hubungannya dengan Amerika Serikat dan Republik Rakyat Tiongkok. Kata Kunci: APEC, Interdependensi, Neoliberal Instutisionalisme, Indonesia, Amerika Serikat, Tiongkok